Validation of mentorship model for newly qualified professional nurses employed in community health care services at Limpopo Province, South Africa - Lekhuleni, M. B.; Khoza, L. B.; Amusa, L. O. (My University, 2013)
Newly qualified professional nurses (NQPNs) allocated to community health care services require the use of validated model to practice independently. Validation was done to adapt and assess if the model is understood and could be implemented by NQPNs and mentors employed in community health care services. The results provided evidence that suggested adoption of the model for mentorship of NQPNs employed in community health care services. To achieve the adequacy of the mentorship model, validation was done by use of validation design involving questionnaires. The population consisted of all NQPNs and mentors employed in Sekhukhune district, Limpopo Province. Purposive sampling was used to select 12 NQPNs and 12 mentors who participated in the study. The NQPNs and mentors agreed on the validation aspects of the model. The adoption and use of the mentorship model by NQPNs and mentors in community health care services is thus recommended.
Article published in: African Journal for Physical, Health Education, Recreation and Dance (AJPHERD), March 2013 (Supplement 1), pp. 204-212.
Keywords: Newly qualified porfessional nurses; Validation; Community health care services; Nurses -- South Africa; Community health nursing -- South Africa